Образи жінок у мистецтві північного Причорномор'я як джерело для реконструкції костюмів скіф'янок - Клочко, Л.С. (Археологія і давня історія України, 2019)
У статті йдеться про пам'ятки торевтики
IV ст. до н. е., на яких представлені жіночі образи.
Вони часто створені за традиціями греко-скіфського мистецтва. Зображення жінок схематичне,
узагальнене, але і так звані «портрети», і сюжетні композиції відбивають особливості вбрання
скіф'янок, тому мають значний інформаційний потенціал для реконструкції різних компонентів убрання. The analysis of female Scythian outer look allows
to imagine the shape of shoulder and waist clothing:
robes with sleeves longer than arm, wide dresses,
draped skirt. Due to high-detailed images we can
determine the way of shaping: observing details of
the images showed two options for tunic-shaped cutting.
Despite the schematics and the generalization in
female imagery, studying toreutics works with female
Scythian images presented is an important foundation
point for reconstructing not only the general look, but
also the ways of creating costumes, their aesthetic, ethnolocal
and semantic specifics.